The predictive value of high school grade point average to academic achievement and career satisfaction of dental graduates - Ayah A. Al-Asmar; Yara Oweis; Noor H. Ismail; Alaa H. A. Sabrah; Islam M. Abd-Raheam (BMC, 2021)
Abstract Background In a country where admission to dental schools is based solely on the cognitive abilities of students, the aim of the study was to investigate the correlation between high school grade point average and graduating academic achievement for dental students; moreover, determine whether a correlation exists between dental students' graduating academic achievement and their career choices and job satisfaction. Methods A five-year retrospective cohort study was conducted at the University of Jordan, involving (828) dental graduates first enrolled between 2010 and 2014. Correlations comparing high school grade point average and graduating academic achievement were done for the total sample composed of (736) students. A short survey was constructed to assess the career choices and job satisfaction for recently graduated dentists and correlate them with their graduating academic achievement. Results Statistically significant but weak positive correlation (0.3) was found between high school grade point average and graduating academic achievement for dental students (p ≤ 0.05). Statistically significant correlations were found between graduating academic achievement and career choices and job satisfaction. Conclusion The significant positive correlation between the high school grade point average and graduating academic achievement of our dental students indicate that our school admission system depending on high school grade point average is a valid system. There was a significant negative correlation between the graduating academic achievement and both the career choices and job satisfaction among fresh graduate dentists in Jordan. This information is required to update the dental school admissions procedures in response to the changing dental educational landscape.